ANALISA DAN DESAIN MAXIMUM POWER POINT TRACKING UNTUK GENERATOR INDUKSI PADA APLIKASI SEPEDA LISTRIK - Hasan, Anshari; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Currently, vehicle transportation is becoming a very important tool in helping humans. Therefore an increase in the volume of the vehicle is very high every year. With so many current vehicles could damage the air cleaner in nature, caused by the combustion of residual Fuel (Fuel oil) the vehicles that emit fumes. Therefore it needs an alternative environment-friendly vehicles with electric bicycles. Electric vehicles currently using permanent magnet motors as their motive. On this research the drivers of electric vehicles use the induction generator who has the advantages i.e. a constant round of and excitation does not need another motor as a driving force. This vehicle is also installed on a system power savings, power saving methods is improved significantly. One of them is MPPT (Maximum Power Point Tracking) used in induction generators. MPPT design is modelled using Matlab/Simulink software. The Matlab simulation has manage to obtain 55.04 volts of MPPT. While the generator output voltage without using the MPPT is amount of 40.84 volts. By using perturb and observe algorithm, it is possible to search the optimum power of generator.Keywords : Generator, Maximum Power Point Tracking (MPPT), Perturb and Observe, Boost Converter, Matlab/ Simulink.